(untitled) (Historia, 2021)
In 1980, as an undergraduate at the University of Pretoria, I was introduced to Historia. The journal had been administered and edited by the university’s History Department since its founding in 1956 by the Historical Association of South Africa to encourage history at school level. After I was appointed as a temporary junior lecturer in the department in 1983, I assisted with the administration of Historia.